Find all School-related info fast with the new School-Specific MBA Forum

It is currently 29 Jul 2015, 22:46
GMAT Club Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

Is p + q > pq ? (1) p > 0 > q (2) |q| = p

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
Director
Director
User avatar
Joined: 07 Nov 2004
Posts: 690
Followers: 5

Kudos [?]: 30 [0], given: 0

Is p + q > pq ? (1) p > 0 > q (2) |q| = p [#permalink] New post 02 Jan 2005, 08:23
00:00
A
B
C
D
E

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 1 sessions
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Is p + q > pq ?

(1) p > 0 > q

(2) |q| = p
Director
Director
User avatar
Joined: 07 Jun 2004
Posts: 614
Location: PA
Followers: 3

Kudos [?]: 329 [0], given: 22

 [#permalink] New post 02 Jan 2005, 08:38
A is ruled out
B is ruled out as | q | = p then q = +/- p

My answer is would be E
Current Student
avatar
Joined: 28 Dec 2004
Posts: 3387
Location: New York City
Schools: Wharton'11 HBS'12
Followers: 14

Kudos [?]: 191 [0], given: 2

Re: DS [#permalink] New post 02 Jan 2005, 10:10
1 is insufficent as p=-q then p+q = 0
2 is insufficent

taking them together

P is positive and q is negative (statement 1)
q= |P| (statement 2)
given 1 and 2 we can conclude that P is equal to negative q, therefor P+q is never greater than PQ (even if P and q were 0s)

I will answer C

gayathri wrote:
Is p + q > pq ?

(1) p > 0 > q

(2) |q| = p
VP
VP
User avatar
Joined: 25 Nov 2004
Posts: 1494
Followers: 6

Kudos [?]: 46 [0], given: 0

Re: DS [#permalink] New post 02 Jan 2005, 14:50
gayathri wrote:
Is p + q > pq ?

(1) p > 0 > q

(2) |q| = p






from (i), p is always +ve and q is always -ve. then,
p+q >=<pq

if we suppose, p=1 and q=-0.1
p+q = 0.9 and pq = -o.1
here, p+q>pq

if p=0.1 and q=-1
p+q = -0.9 and pq = -o.1
here, p+q<pq

so A is insufficient.

from (ii) p is +ve and q is +ve and -ve. it also does not solve the inequality.

if p = 1 and q=0.1
p+q = 1.1 and pq=0.1 i.e. p+q>pq.

if p=2 and q= 3
p+q = 5 and pq=6 i.e. p+q<pq.

if p is +ve and q=-ve, the same results as in (i) result.

Combining togather also doesnot give any solution to the inequality p+q>pq?


therefore E is OA.
Current Student
avatar
Joined: 28 Dec 2004
Posts: 3387
Location: New York City
Schools: Wharton'11 HBS'12
Followers: 14

Kudos [?]: 191 [0], given: 2

Re: DS [#permalink] New post 02 Jan 2005, 16:36
MA can you please explain why combinging the two statements is not enough....

MA wrote:
gayathri wrote:
Is p + q > pq ?

(1) p > 0 > q

(2) |q| = p






from (i), p is always +ve and q is always -ve. then,
p+q >=<pq

if we suppose, p=1 and q=-0.1
p+q = 0.9 and pq = -o.1
here, p+q>pq

if p=0.1 and q=-1
p+q = -0.9 and pq = -o.1
here, p+q<pq

so A is insufficient.

from (ii) p is +ve and q is +ve and -ve. it also does not solve the inequality.

if p = 1 and q=0.1
p+q = 1.1 and pq=0.1 i.e. p+q>pq.

if p=2 and q= 3
p+q = 5 and pq=6 i.e. p+q<pq.

if p is +ve and q=-ve, the same results as in (i) result.

Combining togather also doesnot give any solution to the inequality p+q>pq?


therefore E is OA.
Director
Director
User avatar
Joined: 07 Jun 2004
Posts: 614
Location: PA
Followers: 3

Kudos [?]: 329 [0], given: 22

 [#permalink] New post 02 Jan 2005, 17:03
guys what does the acronym OA stand for ??
Director
Director
User avatar
Joined: 07 Nov 2004
Posts: 690
Followers: 5

Kudos [?]: 30 [0], given: 0

 [#permalink] New post 02 Jan 2005, 18:32
OA is C

Explanation given is...

The correct response is (C). Statement (1) alone establishes that pq < 0, because the product of a positive number and a negative number is always negative. If you subsetitute integers for p and q, the answer to the question is always "yes." However, if you substitute fractional values (between -1 and 1) for p and q, in some cases the answer to the question is "no." For example, if p = 1/4 and q = -1/2 , p + q = -1/4 while pq = -1/8 , and therefore p + q < pq. Thus, statement (1) alone is insufficient to answer the question.

Statement (2) alone is also insufficient to answer the question. Again, the answer to the question depends on the values of p and q. For example, If p = 3 and q = -3, then p + q > pq. But if p = 3 and q = 3, then is p + q < pq.

Statements (1) and (2) together are sufficient to answer the question. Together, statements (1) and (2) establish that q is the same non-zero number as p, except negative instead of positive. Therefore, p + q will always equal 0, while pq will always be negative. Accordingly, the answer to the question will always be "yes."
VP
VP
User avatar
Joined: 25 Nov 2004
Posts: 1494
Followers: 6

Kudos [?]: 46 [0], given: 0

 [#permalink] New post 02 Jan 2005, 18:44
gayathri wrote:
OA is C

Explanation given is...

The correct response is (C). Statement (1) alone establishes that pq < 0, because the product of a positive number and a negative number is always negative. If you subsetitute integers for p and q, the answer to the question is always "yes." However, if you substitute fractional values (between -1 and 1) for p and q, in some cases the answer to the question is "no." For example, if p = 1/4 and q = -1/2 , p + q = -1/4 while pq = -1/8 , and therefore p + q < pq. Thus, statement (1) alone is insufficient to answer the question.

Statement (2) alone is also insufficient to answer the question. Again, the answer to the question depends on the values of p and q. For example, If p = 3 and q = -3, then p + q > pq. But if p = 3 and q = 3, then is p + q < pq.

Statements (1) and (2) together are sufficient to answer the question. Together, statements (1) and (2) establish that q is the same non-zero number as p, except negative instead of positive. Therefore, p + q will always equal 0, while pq will always be negative. Accordingly, the answer to the question will always be "yes."



agreed. i forget the information, modulas q = p.
  [#permalink] 02 Jan 2005, 18:44
Display posts from previous: Sort by

Is p + q > pq ? (1) p > 0 > q (2) |q| = p

  Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Privacy Policy| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group and phpBB SEO

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.